GAMBARAN KADAR TRIGLISERID AKSEPTOR KB SUNTIK DMPA YANG DILAKUKAN BEKAM BASAH - Amin Samiasih; Tri Hartiti (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2014)
Background: Medroksi Depo Progesterone Acetate (DMPA) use in central Java is56.88% . DMPA  used in Indonesia because the failure rate of less than 1%, might forget asmall, high reversibility, does not interfere with intercourse, use of a long period of time (along-acting contraceptive steroids) (BKKBN, 2012, Ganiswara SG, 2008). Research Hartiti T2010, the longer use of DMPA Injectable  increased triglyceride levels. Triglycerides contributeto risk factors for atherosclerosis and coronary heart disease (CHD) when accompanied bydecreased levels of HDL. (Mitrovska S, Jovanova S, Matthiesen I, Libermans C, 2009, LihChen Yun Wing, Ya Chi Chen, Yu Yin Shih, Jung Chien Cheng, Jiuan Yiu Lin, and Jyh JiangMeeii 2008). Wet cupping complementary therapies proven to reduce LDL cholesterol tonormal males (Farahmand SK, LZ Gang, Saghebi SA, Mohammadi M, Mohammadi S,Mohammadi G, et al 2012). Wet Cupping lower cholesterol, triglycerides and uric acid inpatients with migraine in Demak (Samiasih A, and Hartiti T, 2013). Obaject of research: toprove the effect of wet cupping on injectable DMPA acceptors triglycerides. Results: Levels oftriglycerides before cupping mean 305mg / dl, minimum 250mg / dl and a maximum of 370mg /dl with a standard deviation of 33.9. Triglyceride levels after cupping mean 272 mg / dl, aminimum of 200 mg / dl and a maximum of 350 mg / dl with a standard deviation of 51.5. Thetest results stated Pair T Test p value 0.001 which means there wet cupping effect ontriglyceride levels injectable DMPA acceptors. Conclusions wet cupping decreased triglyceridelevel on DMPA contaception injection use. Keywords: DMPA, wet cupping, triglycerides